Handgrip Strength is Related to Regional Brain Volumes in a Cohort of Cognitively Impaired Older Adults with Confirmed Amyloid Burden. (20th December 2022) - Meysami, Somayeh; Raji, Cyrus A.; Popa, Emily S.; Ganapathi, Aarthi S.; Bookheimer, Tess; Slyapich, Colby B.; Pierce, Kyron P.; Richards, Casey J.; Gill, Jaya M.; Lampa, Melanie G.; Rapozo, Molly K.; Hodes, John F.; et al.
Abstract: Background: Handgrip strength is important for performing activities of daily living[1]. In older adults, weaker handgrip strength and asymmetry are associated with poorer cognition. o better understand mechanisms, we sought to quantify the relationship between handgrip strength and regional volumes quantified on brain MR imaging. Method: We selected 32 participants (mean age=70.8±7.3 [range 57‐89] years, 53.1% female, 90.6% right‐handed, mean body mass index BMI=23.9±4.1) from the Pacific Brain Health Center at Providence St. John's Health Center, with Alzheimer dementia biomarker evidence of amyloidosis[2]. Mean Montreal Cognitive Assessment score for all participants was 21.3±3.8 points. Handgrip strength on dominant and non‐dominant hands was measured using the NIH Motor Toolbox[3] as part of a cognitive fitness assessment using a hydraulic hand dynamometer. The resulting scores included handgrip strength and percentile comparisons to normative data. Asymmetry scores were calculated. Regional brain volumes, including lobar structures and the hippocampus, were measured from T1‐weighted MR images using Neuroreader[4]. Partial correlations (rp ), adjusting for age, sex, BMI and total intracranial volume modeled handgrip strength, asymmetry, and brain volumes with a significance threshold of p<0.05. Result: In the dominant hand, higher handgrip strength scores and percentiles were associated with larger volumes in the left frontal lobe (rp =+0.51, p=0.007; rp =+0.47, p=0.01) and right parietal lobe (rp =+0.40, p=0.03; rp =+0.39, p=0.04). In the non‐dominant hand, higher handgrip strength score and percentiles were associated with smaller total cerebral spinal fluid (CSF) volume (rp =‐0.55, p=0.004; rp =‐0.52, p =0.006) and larger volumes within the left hippocampus (rp =+0.45, p=0.01; rp =+.43, p=0.02), right hippocampus (rp =+0.47, p=0.01; rp =+0.43, p=0.02), and right parietal lobe (rp =+0.39, p=0.04; rp =+0.44, p=0.02). Handgrip strength asymmetry was inversely related to right hippocampal volume (rp =‐0.58, p=0.002) and positively correlated to CSF volume (rp =+0.39, p=0.04). Conclusion: Greater handgrip strength was related to larger regional brain volumes. A higher number of brain regions were related to the non‐dominant hand. Asymmetry was associated with lower right hippocampal volume and higher CSF volume. Interventions focused on improving handgrip strength may seek to include quantified brain volumes on MR imaging as endpoints.